Breast Cancer in Transgenders: Narrative Review - Goyal, Pankaj; Jain, Praveen; Agrawal, Chaturbhuj; Jain, Sneha Bothra; Talwar, Vineet; Batra, Ullas; Goyal, Sumit; Maheshwari, Udip; Chaudhari, Krushna; Goel, Varun; BP, Amrith; Doval, Dinesh Chandra (Indian Journal of Medical and Paediatric Oncology, 2022)
The molecular pathogenesis of breast cancer (BC), the second most common cancer, varies significantly between sexes, with minimal data in the transgender population. The overall prevalence of BC in transgenders is estimated to be 0.02%. Besides experiencing social disparities, transgenders have to face a lot of discrimination in the healthcare system. Adversities faced, along with the urge to identify with physical attributes to the gender felt by them, forces transgenders to use non-prescribed hormones. Gender affirming hormone therapy (GAHT) is a key feature of transition-related care, rehabbing mental health, and the quality of life of transgenders, but at the expense of their health. Studies have reported that GAHT is associated with severe health conditions such as cancer in transgenders. Estrogens and testosterone are associated with a moderate risk of developing BC. The types of BC diagnosed in transgenders after cross-sex hormone therapy include invasive ductal and neuroendocrine carcinoma, in addition to tubular adenocarcinoma. Although diagnosed at an age earlier compared with ciswomen, BC screening recommendations for transgenders are the same as for ciswomen. This review studies in detail the types of transgenders, their characteristics, different types of breast cancers associated, issues faced while treatment, and their best possible solutions. We also hope to have well-designed research in the future, which will fill the existing gaps in knowledge and provide scientific insight into the transgender population and issues related to their health. There are no international guidelines on screening and management of transgender patients but it appears that breast screening before cosmetic mastectomy, exposure to hormonal therapy for more than 5 years, and as per natal women screening guidelines should be offered to the patient with detailed discussion on the harms and benefits of the same.
Keywords: transgenders; breast cancer; transwomen; transmen; gender-affirming hormone therapy